A non-language-specific speech test to evaluate the speech of cleft patients from different language and cultural backgrounds – A pilot study. Issue 1 (January 2018) - Kleinfeld, Heiko Cornelis; Foldenauer, Ann Christina; Ghassemi, Mehrangiz; Modabber, Ali; Movahedian Attar, Bijan; Ahmed, Syed Sayeed; Neuschaefer-Rube, Christiane; Ghassemi, Alireza
Abstract: Cleft speech tests are not universally available. We developed a tool to fill this gap, especially in the context of a cleft mission setting. We performed a pilot study to evaluate the test's ability to differentiate between the speech of cleft patients and healthy individuals from three different language backgrounds. We used 78 made-up, nonsensical syllables to evaluate hypernasality, nasal emissions, and consonant errors. Cleft ( n  = 41) and non-cleft ( n  = 39) individuals from three countries were included in this study. Two speech and language pathologists, blinded to the examination, rated the audio recording independently. Patients from Germany ( n  = 12; mean age 15.2), Iran ( n  = 14; mean age 7), and India ( n  = 15; mean age 14.7 years) were evaluated. We observed a significant difference in each category ( p  < 0.05) between patients and control subjects of the same language and cultural background. Hypernasality was affected the most. The test proved to possess the correct phonetic characteristics to reveal and provoke relevant cleft speech pathologies independent of cultural and language backgrounds. The test sounds posed no articulatory difficulties to non-cleft individuals, with some exceptions regarding non-specific consonant errors. A comparison with other existing tests will further illuminate its value as a speech test.